Living with coastal hazards: place attachment and risk perception at Faro beach - Domingues, Rita Isabel de Oliveira Soares Branco (2022)
Risk perception and place attachment are constructs frequently studied in the context of environmental hazards. Risk perception is a subjective and emotional judgement about the severity of a risk, and it may be influenced by place attachment, the emotional connection between an individual and a specific place. The interplay between these constructs influences how individuals deal with risks. Faro Beach is a vulnerable and heavily urbanized settlement in the Ria Formosa barrier island system, exposed to beach erosion and overwash caused by storms, that have resulted in house and road destruction. However, residents, mainly fishermen and their families, have accepted the risks in exchange for benefits that they perceive as largely exceeding potential personal damages. Although residents are aware of the coastal hazards impacting the area, they do not seem worried or prepared to deal with the associated risks, and they refuse to relocate to safer locations. The main goal of this thesis is to understand the psychological variables, particularly risk perception and place attachment, that influence residents’ perceptions towards coastal risks. Both qualitative and quantitative approaches were used. Content analysis of semi-structured interviews with selected stakeholders allowed the development of self-report questionnaires that were applied to Faro Beach residents. Quantitative data were analysed using descriptive and correlational statistics, and relationships between constructs were tested with partial least squares structural equation modelling. Two psychometric instruments aimed at measuring risk perception and sense of place were also developed and validated. Overall, it was confirmed that Faro Beach residents are aware of the risks they face, most of them have witnessed coastal hazards, but they feel safe living at the beach. A strong emotional attachment to the place, influenced by a long residence time, familial heritage, and social ties, is at the root of residents’ low risk perception and unwillingness to relocate to safer grounds. In addition, an optimism bias and the perception that threats are distant in time prevent the adoption of effective preparedness measures to deal with a potential disaster. Despite some limitations, mainly related to the small samples used, this thesis made significant contributions to environmental psychology and has relevant implications for coastal management. Keywords: place attachment; risk perception; preparedness; coastal risks; coastal management; environmental psychology.